APLIKASI METODE SAW DALAM PEMILIHAN JURUSAN MENGGUNAKAN FUZZY MULTIPLE ATRIBUTE DECISION MAKING PADA SMA N.1 KOTO BARU KABUPATEN DHARMASRAYA - Zefri Yenni; Heti Iskandar (Jurnal Teknologi Informasi dan Pendidikan, 2016)
Education is one of the many areas that utilize technology to gain information. Selection of the majors on SMA N 1 Koto Baru still using manual processes using Microsoft office excel, this course requires a lot of time and energy. Therefore, to facilitate the school in the electoral process and to minimize majors operating costs, designing a decision support system for the selection of majors that can be used by the school to quickly and easily and can provide accurate information about the selection result graders majoring in SMA N 1 Koto Baru. Decision support system design election this department using fuzzy multiple attribute decision making with methods of saw. Using the model of the ASI (flow of information systems and the use of programing languages supported PHP MySQL database makes this system into a decision support system that can assist users in selecting majors in accordance with the wishes of students